Entry inhibition of hepatitis B virus using cyclosporin O derivatives with peptoid side chain incorporation. (15th August 2022) - Lee, Dongjae; Kang, Jung-Ah; Lim, Chanseok; Bae, Sunjae; Choi, Jieun; Park, Minji; Kim, Yong-Chul; Cho, Yuri; Park, Sung-Gyoo; Seo, Jiwon
Graphical abstract: Abstract: Hepatitis B virus (HBV) infection is a serious worldwide health problem causing liver cirrhosis and hepatocellular carcinoma. The development of novel therapeutics targeting distinct steps of the HBV life cycle and combination therapy with approved drugs (i.e., nucleot(s)ides, interferon-α) are considered effective strategies for curing HBV. Among these strategies is the development of entry inhibitors that interfere with the host entry step of HBV to prevent viral infection and transmission. Herein, we generated a novel library of cyclosporin O (CsO) derivatives that incorporate peptoid side chains. Twenty-two CsO derivatives were evaluated for membrane permeability, cytotoxicity, and in vitro HBV entry inhibitory activity. The lead compound (i.e., compound 21 ) showed the greatest potency in the in vitro HBV entry inhibition assay (IC50 = 0.36 ± 0.01 μM) with minimal cytotoxicity. Our peptide-peptoid hybrid CsO scaffold can readily expand chemical diversity and is applicable for screening various targets requiring macrocyclic chemical entities.